Uniform deposition of Ag nanoparticles on ZnO nanorod arrays grown on polyimide/Ag nanofibers by electrospinning, hydrothermal, and photoreduction processes. (5th November 2019) - Lu, Fang; Wang, Jinguang; Chang, Zhenjun; Zeng, Jing
Abstract: Advanced functional hierarchical nanostructures with controllable morphologies at the three-dimensional nanosize level have attracted significant attention owing to their potential applications. In this study, a simple and efficient method was developed for preparing hexagonal wurtzite zinc oxide (ZnO) nanorod arrays on polyimide (PI) and PI/Ag nanofibers for obtaining brushed-shaped PI/ZnO and (PI/Ag)/ZnO by combining electrospinning and hydrothermal reaction processes. The Ag nanoparticles were deposited on the ZnO nanorods for preparing (PI/Ag)/ZnO-Ag using a photoreduction method. The surface morphology, structure, composition, and photocatalytic properties of these structures were characterised by scanning electron microscopy, X-ray diffraction, X-ray photoelectron spectroscopy, and ultraviolet–visible spectroscopy. Compared with PI/ZnO, the (PI/Ag)/ZnO-Ag hierarchical nanofibers exhibited improved photocatalytic degradation of methylene blue dye. Graphical abstract: Unlabelled Image Highlights: Well-ordered ZnO nanorod arrays on polyimide (PI) and PI/Ag nanofibers were fabricated. Ag nanoparticles on (PI/Ag)/ZnO surface were prepared via photoreduction method. (PI/Ag)/ZnO-Ag hybrid nanofibers possess better ability to photodegradate MB compared with PI/ZnO and (PI/Ag)/ZnO. The hierarchical nanostructure is ideal for hindering the recombination of electrons and holes.